(untitled) (Acta Education, 2023)
this article discusses the use of artificial intelligence in education. The authors describe the current state and prospects for the development of this direction. The article analyzes the main problems and prospects of using artificial intelligence in the educational process, and also describes the possibilities of using AI to individualize learning and evaluate students’ knowledge. In conclusion, the authors emphasize the need to develop research in the field of AI in education in order to improve the quality of education and increase the efficiency of the educational process. Description of the current and future possibilities of using AI in education makes the article relevant and interesting for everyone who is interested in modern technologies in education